2006
DOI: 10.1007/s00261-006-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient small bowel intussusceptions: ultrasound findings and clinical significance

Abstract: Incidentally detected, small bowel intussusceptions without an identifiable pathological lead point, with a normal wall thickness, a length of less than 3.5 cm, normal nondilated proximal bowel and normal vascularity on color Doppler reduce spontaneously and are of no clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
2
24
0
8
Order By: Relevance
“…In addition, with the development and wide application of ultrasound technology, the presence of temporary or transient small bowel intussusceptions has become clinically apparent [1,4,5,8,11]. Doi et al [8] have suggested the term benign small bowel intussusception to describe those that are found incidentally and/or resolve spontaneously.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, with the development and wide application of ultrasound technology, the presence of temporary or transient small bowel intussusceptions has become clinically apparent [1,4,5,8,11]. Doi et al [8] have suggested the term benign small bowel intussusception to describe those that are found incidentally and/or resolve spontaneously.…”
Section: Discussionmentioning
confidence: 97%
“…Kim [4] reviewed the ultrasound findings of 34 SBIs diagnosed in 32 infants and children and found that transient SBIs typically exhibited a small size (mean diameter 1.5 cm) without wall swelling, a short segment (mean length 1.8 cm), preserved wall motion, and the absence of a lead point. Mateen et al [11] reviewed the records of 108 consecutive patients (adults and children) with intestinal intussusceptions, of which 41 were diagnosed as transient SBIs. They found that SBIs without an identifiable pathological lead point, normal wall thickness, normal non-dilated proximal bowel, normal vascularity on color Doppler ultrasound, and a length of <3.5 cm reduced spontaneously and were not of clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Typical findings of benign SBI associated with spontaneous reduction on US are: a) small outer diameter (<2.5 cm), b) short segmental invagination (<3 cm), c) peristaltic wall motion, and d) absence of any visible pathological lead point. [5,7,9] The incidence of pathological lead point in patients with SBI is low according to Kornecki et al [6] However, Ko et al 2 found lead point in 56% of the patients with SBI requiring surgical exploration. There are reports of spontaneous reduction of SBI even in presence of lead points, i.e., in patients with polyp, perpura.…”
Section: Discussionmentioning
confidence: 98%
“…However, patients with recurrent or multiple intussusceptions and those with persistent symptoms should undergo surgical exploration. [7][8][9] Ko et al [2] has reported three patients with idiopathic ileoileal intussusception developing delayed peforation after 6, 32, and 99 days. So it is important to closely follow-up the patients with SBI for several months.…”
Section: Discussionmentioning
confidence: 99%
“…Elles sont rarement secondaires [62]. Elles se réduisent spontanément en quelques minutes dans la très grande majorité des cas [62], notamment lorsqu'elles sont de petit diamètre (< 2 cm), de moins de 3,5 cm de long avec une vascularisation normale au Doppler et sans oedème de la paroi [63,64]. Chez les enfants symptomatiques, un contrôle échographique est recommandé [23,65].…”
Section: éChographieunclassified